2013
DOI: 10.1016/j.jretconser.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-town shopping and its induced CO2-emissions

Abstract: Planning policies in several European countries have aimed at hindering the expansion of out-of-town shopping centers. One argument for this is concern for the increase in transport and a resulting increase in environmental externalities such as CO 2 -emissions. This concern is weakly founded in science as few studies have attempted to measure CO 2 -emissions of shopping trips as a function of the location of the shopping centers. In this paper we conduct a counter-factual analysis comparing downtown, edge-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Moreover, the demand for high-end shops and products generates longer travel distances to commercial centers in the downtown region and in the suburbs, especially to outlet malls emerging in Hunnan. Consistent with our results, Carling et al [50] found that shopping carbon emissions are influenced by the spatial distribution of different types of retail centers. Therefore, we recommend that the type of retail center be considered in the spatial configuration of commercial centers.…”
Section: Retail Type and Energy Consumptionsupporting
confidence: 93%
“…Moreover, the demand for high-end shops and products generates longer travel distances to commercial centers in the downtown region and in the suburbs, especially to outlet malls emerging in Hunnan. Consistent with our results, Carling et al [50] found that shopping carbon emissions are influenced by the spatial distribution of different types of retail centers. Therefore, we recommend that the type of retail center be considered in the spatial configuration of commercial centers.…”
Section: Retail Type and Energy Consumptionsupporting
confidence: 93%
“…For instance, some studies tried to segment trajectories using an arbitrary specified speed threshold [4] or elapsed time threshold [5]. Some studies estimated CO 2 emissions from trajectories and applied them to sustainable location planning [6] and market analysis for the retail sector [7]. A recent study explored the relationship between human activities and landscape patterns [8], and studies more relevant to our work focused on mining human activity patterns [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, as noted earlier an in-depth study of consumer shopping trip behavior was conducted in Borlänge, a centrally located city in the region under study (Carling et al 2013b;Jia et al 2013), where some 250 volunteer car owners were tracked for two months using GPS, and the typical travel behavior for trips to a store selling durable goods such as consumer electronics was to drive the shortest route from the home to the store, and then back again. Consequently, we approximated shopping-related trips using the shortest route in our analysis.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Stead (1999), based on data from the 1989-1991 National Travel Survey, suggested using road distance as a proxy for vehicle emissions because of the ease of collecting and computing it. Previous work in Dalarna indicates that, while intersections and arterial roads imply higher emissions, emissions crucially depend on road distance (Carling, Håkansson, and Jia, 2013b;Jia, Carling, and Håkansson 2013). It is an approximation to replace CO 2 emissions with road distance, though it is a fairly good one, as also demonstrated in a sensitivity analysis by Carling et al (2015a).…”
mentioning
confidence: 93%